Perilaku Tabungan ASEAN 5, Jepang, Cina, Korea, dan Implikasinya terhadap Ketidakseimbangan Global - Safuan, Sugiharso; Sari, Heidy Ruswita (Jurnal Ekonomi dan Pembangunan Indonesia, 2012)
The study examines saving behavior in ASEAN 5+3 namely Indonesia, Malaysia, Singapore, Thailand, Philippines, Japan, China, and Korea during 1991-2007 and its implication toward global imbalances. By using fixed effect panel data regression, this research shows that government spending, interest rate and inflation, financial development through private domestic credit and stock market capitalization along with the 1997 Asian crisis significantly affect the saving behavior. As a result, a macroeconomic stability through interest rate and inflation, the reinforcement of financial development and crisis anticipation policy are required to support global re-balancing through global saving redistribution.